HUBUNGAN STATUS GIZI DENGAN DERAJAT KEPARAHAN PNEUMONIA PADA BALITA - Suharni, Suharni; Resdamia Aprilia; Efriza, Efriza; Rendri Bayu Hansah; Muhammad Rizki Saputra; Letvi Mona; Yanti Fitri Yasa (Yayasan Nusantara Hasana Berdikari, 2025)
Pneumonia is a lower respiratory tract infection and a leading cause of death in children. It ranks as the primary cause of child mortality, accounting for 15% of all deaths in children under five, with 740,180 deaths reported in 2019. West Sumatra is the province with the second-highest number of pneumonia cases among children under five on Sumatra Island. This study aims to analyze the frequency distribution and characteristics of pneumonia cases in children under five and examine the relationship between nutritional status and the severity of pneumonia in children under five at RSUP Dr. M. Djamil Padang in 2022–2023. This observational analytic study employed a cross-sectional approach, utilizing secondary data from the medical records of pediatric pneumonia patients. Data collection was conducted in October 2024. The population consisted of all children under five diagnosed with pneumonia at RSUP Dr. M. Djamil Padang from 2022 to 2023. A total sampling technique was used, resulting in 52 respondents. Data analysis included univariate and bivariate methods, with the Chi-square test employed to determine statistical significance. The study found that most pneumonia cases occurred in children aged 1–11 months (66,0%) and were more common in males (57.7%). The majority of children had good nutritional status (64,0%), and (58,0%) experienced mild pneumonia. Bivariate analysis revealed a significant relationship between nutritional status and pneumonia severity (p = 0.033). This study concludes that nutritional status is significantly associated with the severity of pneumonia in children under five at RSUP Dr. M. Djamil Padang during 2022– 2023.